(untitled) (International Journal of Food and Nutritional Sciences, 2021)
A halo is an optical and atmospheric phenomenon produced by light, from the Sun or Moon interacting with millions of tiny ice crystals associated with the cirrus cloud family which are form in the air. Among the best known halo types are the circular halo (properly called the 22° halo), light pillars, and sun dogs, but many others occur; some are fairly common while others are extremely rare. A halo is a ring or light that forms around the sun or moon as the sun or moon light refracts off ice crystals present in a thin veil of cirrus clouds. The halo is usually seen as a bright, white ring although sometimes it can have color.